Pelatihan Startup untuk Menyiapkan Pengusaha Muda Berbasis Pendidikan - Tera Noviantiningtyas Ripto saputri; Qonita Nur Rohmania; Dodik Nuryuono (SAP (Susunan Artikel Pendidikan), 2021)
Education plays a role in the development of the Millennium Development Goals (MDGs), namely shaping human resources. The focus of human resources here is Vocational High School (SMK) students. Entering the era of the Industrial Revolution 4.0, the application of IT-based learning is applied to support sustainable development and is expected to be a provision for vocational students in overcoming problems in society and having an impact on their economic, social and environmental life. Many vocational graduates are still unemployed. The causes of unemployment are the lack of opportunities, low critical thinking skills, and not having the courage to take risks at work. Solution to reduce unemployment is by teaching and developing startups within the scope of the school, namely education. Startups are expected to be able to prepare students for the world of work and the world of industry. The provision of startup-based entrepreneurship provisions can be used as provisions in the world of work for the community, especially SMK graduates.. One solution to the government's hope of increasing the number of young entrepreneurs is a startup.